A multi-agent platform for the deployment of ambient systems. (2018) - Fallah-Seghrouchni, Amal El; Piette, Ferdinand; Caval, Costin; Taillibert, Patrick
With the explosion of the internet of things, it is critical to decide which connected devices can be used by an application in order to achieve its objectives, while maintaining user information privacy. In this paper we propose a solution for the configuration and the deployment of distributed applications in smart environments that takes into consideration device heterogeneity, the dynamics of the environment and the need for resource privacy. The key points of our solution are: 1) an ontology allowing the description of the environment (the hardware entities and the applications to be deployed) using graphs; 2) a distributed algorithm capable of reasoning on these descriptions to decide which hardware entities of the infrastructure have to be used to deploy a specific application; 3) a goal-directed multi-agent system as a well-adapted paradigm to provide a clear separation between the applicative and the infrastructure layers.